2019
DOI: 10.1182/blood-2019-123345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Major Depression Among Cancer Patients: Single Center Tertiary Care Hospital Experience from Lahore, Pakistan

Abstract: Introduction: Major depressive disorder (MDD) often goes unrecognized in cancer patients. Some symptoms of major depression mimic signs and symptoms of malignancy due to which it often remains under-diagnosed. Depression has a contributing role in increasing the morbidity of cancer patients which if diagnosed and managed early in the treatment course can have a positive impact on cancer patients. This study focuses on determining the prevalence of major depression among cancer patients admitted in a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cardoso et al (2016) found that having a more advanced cancer stage increase the vulnerability for depression. Farooqui et al (2019) reported that patients in the fourth stage and in the third stage of disease had more odds to have depression as compared to those in the second stage. Fradelos et al (2017) found that among patients diagnosed with breast cancer, those in the advanced stages were more prone to experience depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardoso et al (2016) found that having a more advanced cancer stage increase the vulnerability for depression. Farooqui et al (2019) reported that patients in the fourth stage and in the third stage of disease had more odds to have depression as compared to those in the second stage. Fradelos et al (2017) found that among patients diagnosed with breast cancer, those in the advanced stages were more prone to experience depression.…”
Section: Discussionmentioning
confidence: 99%
“…Depression negatively affects quality of life, self‐care, coping strength, and compliance to treatment in cancer. With the ability to affect the severity and course of the disease over time, depression can also cause serious problems, such as suicide (Farooqui et al, 2019; Saracino & Nelson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They confirm our and other reports showing a significant association between anxiety and depression, where more than half of patients exhibited both mental health problems (Boehm, Cramer, Staroszynski and Ostermann, 2014;Pasquini and Biondi, 2007;Smith, 2015). The reported prevalence of depression in cancer patients varies greatly across the studies in the Middle-East region, ranging from 16.1% to 57.1% (Nikbakhsh, Moudi, Abbasian and Khafri 2014;Akel et al, 2017;El-Hadidy et al 2012;Abuelgasim et al, 2016;Bener , Alsulaiman, Doodson and El Ayoubi HR, 2016;Wondimagegnehu, Abebe, Abraha and Teferra, 2019;Farooqui et al, 2019;Khalil et al, 2016;Malak, Tawalbeh and Al-Amer RM, 2021;Shaheen et al, 2015). This variation can be linked to a number of reasons such as different settings, study population, cancer types, cancer stage and the screening tools.…”
Section: Cancer Types and Treatmentsmentioning
confidence: 99%